Metalloproteomics: principles, challenges and applications to neurodegeneration - Roberts, Blaine R.; Lothian, Amber; Hare, Dominic J.; Masters, Colin L.; Ryan, Timothy M.; Grimm, Rudolf (Frontiers in Aging Neuroscience, 2013)
Trace elements are required for a variety of normal biological functions. As our understanding of neurodegenerative disease advances we are identifying a number of metalloenzymes involved in disease process. Thus, the future of metals in neurobiology will rely more on detailed information regarding what metalloenzymes are present and how they are involved in the pathophysiology of disease. To gain this detailed information, we will rely less on bulk measures of the amount of a trace elements in a particular tissue and turn to metalloproteomic techniques to help elucidate both metalloprotein structure and function. Recent advances in metalloproteomics will translate to a richer understanding of the mechanism and precise role of metalloenzymes and proteins in the brain.